The Impact of Corona Virus on Supply Chain of Halal Tourism Management in West Nusa Tenggara - Jaelani, Abdul Kadir; Ketut Rachmi Handayani, I Gusti Ayu; Karjoko, Lego (International Journal of Supply Chain Management, 2020)
Abstract— This study aims to explain the impact of the corona virus on the supply chain of halal tourism management in West Nusa Tenggara. The type of research used is normative legal research. This study is descriptive. The type of data used is secondary data. Secondary data collection techniques were obtained through literature review. The primary and secondary data were analyzed qualitatively. The results showed that, first, the most dominant impact occurred on trade and tourism. During January to March 2020, there was a decline in imports and exports from and to China. The number of Chinese tourists also dropped quite dramatically. Efforts that can be made to overcome this include diversification of export shares to other countries; increase domestic production and consumption; and increase domestic tourism and tourists from outside China. Second, the supply chain of halal tourism management through Regional Regulation Number 2 of 2016 on Halal Tourism has not solved the problems of regional tourism such as good environmental maintenance from the increasingly damaged biology resource crisis, the deforestation, the limited water resources, soil erosion, sedimentation, abrasion on the cost, coral reef damage, littering 53% or about 250 ton plastic waste every day.  Even, this regional regulation is in contrary to the higher laws and religious nuances.